Application of eCommerce Technology as Online Sales Media - Widhy Wahyani; Sanny Andjar Sari (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2022)
The increasingly rapid use of the internet as an impact of information technology infrastructure which in fact is able to encourage the birth of a new paradigm in the process, namely the use of the internet and information and communication technology infrastructure. In the midst of the widespread use of e-commerce technology today, it has also penetrated the MSME business sector. The purpose of this research is to implement e-commerce technology that functions as an online sales medium, to find out the obstacles faced in implementing e-commerce technology, and to know the advantages and disadvantages of e-commerce implementation. The object of this research is MSME Various Foods "ALBAR", Kebonagung, Malang, East Java, which is engaged in food and baverage. The MSMEs were initially observed that this research had not yet fully started digital transformation even though they had used social media to promote products. One of the obstacles that arise is because business owners as well as business people do not fully understand the e_commerce platform and its potential. Business people not only want to promote sales, but also want to make online sales transactions. By applying e-commerce technology to MSMEs, it is hoped that it can help by providing solutions for MSME actors in selling products during the COVID-19 pandemic, so that the income from the "ALBAR" Various Food business does not drop drastically even though on the one hand it has to reduce direct contact with buyers. Keyword: e_commerce, social distancing, teknologi, penjualan online, COVID-19.